The Effectiveness of Group Counseling in Improving Academic Resilience in Classroom Students XI SMA UISU Siantar - Yunita Yunita; Muhammad Abdul Aziz (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Academic resilience is a student's ability to face academic difficulties, persist, and recover from failure. This study aims to test the effectiveness of group counseling in improving the academic resilience of eleventh-grade students at UISU Siantar High School. The method used was a quasi-experimental with a pre-test post-test one group design. The research subjects were 10 students with low to moderate levels of academic resilience, selected using a purposive sampling technique. The research instrument used an academic resilience scale based on Martin and Marsh's theory consisting of 25 valid items with a Cronbach's Alpha reliability of 0.876. The group counseling intervention was conducted in four sessions with an approach that focused on developing self-efficacy, adaptive help-seeking, self-regulation, and persistence. The results showed a significant increase in students' academic resilience after participating in group counseling, with a paired sample t-test showing a value of t = -2.858 and p = 0.019 (p < 0.05). The empirical mean increased from 73,200 in the pretest to 80,200 in the posttest, with a hypothetical mean of 62,500. Thus, group counseling proved effective as an intervention method to help students cope with academic stress and increase learning motivation. This study provides practical implications for guidance and counseling teachers in developing systematic intervention programs to improve students' academic resilience.